A Place Between School and Home: Exploring the Place of Shadow Education in Students' Academic Lives in the Netherlands - Daury Jansen; Louise Elffers; Monique L. L. Volman (Karolinum Press, 2020)
Worldwide, the use of private supplementary tutoring, commonly referred to as shadow education, has become increasingly prevalent since the turn of the millennium. Recently, participation rates in the Netherlands have substantially increased. This paper aims to explore the place of shadow education in students' academic lives by studying the goals and experienced benefits that students identify. Data were collected through 37 semi-structured interviews with tutored students in secondary education in the Netherlands. Our findings indicate that students conceived of shadow education as a skill-building institution to which they turned to for self-study, to receive career support, and to boost their performance. Students' reflections reveal that shadow education builds upon and extends - but does not replace - learning activities at home and school. Based on our findings, we discuss how shadow education can function as a "third place" between school and home, occupying an increasingly prominent position in students' academic lives.